The Influence of Motivation, Work Environment, Communication, and Work Discipline on Employee Performance in CV. Buana Mas Kediri - Setyaji Sasongko; Abu Talkah (Otonomi, 2022)
Buana Mas is a company engaged in the distribution of Stationery, Cooking Oil, Seasonings and Batteries. Of course, with the spirit of work and reliable service by experienced professionals in their fields, they are able to provide solutions and contribute to consumers. To realize the company's goal of achieving a high level of productivity, employees who have high performance are needed to achieve this. Human resources (HR) is the most important asset in the company, because HR manages all the resources owned by the company. The achievement of the company's goals is also determined by the quality of its human resources. The purpose of this study was to determine and analyze the effect of motivation, work discipline, communication, and work environment simultaneously on employee productivity. Based on the results of research and discussion in previous chapters, it can be concluded as follows: There is an influence between motivation on employee work productivity. This is evidenced by the t count of 3.491 with a significance of 0.002 <0.05. There is an influence between work discipline on employee work productivity. This is evidenced by the t count of 2.275 with a significance of 0.030 < 0.05. There is an influence between work communication on employee work productivity. This is evidenced by the t count of 2.213 with a significance of 0.035 < 0.05. There is an influence between the work environment on employee work productivity. This is evidenced by the t count of 3.564 with a significance of 0.001 < 0.05. There is a simultaneous effect of motivation, work discipline, communication, and work environment variables on employee productivity. This is evidenced by the calculated F value of 137.963 with a significance value of 0.000 <0.05. Based on the description above, the suggestion from the author is. Based on the results of the study it is known that the work discipline variable gives the lowest contribution compared to other variables, so it is hoped that the company will improve employee work discipline by providing rewards for those who are disciplined and punishment for those who violate.